The influence of Ni concentration on the mechanical properties of Ni doped CrAlSiN coatings - Chan, Kwan Yee. (2013)
Thin film coatings are commonly used in various applications and its performance is of high importance. The mechanical properties such as hardness often evaluated to determine the lifetime of a material. CrAlSiN is hard material and it is the successor of various thin film coatings such as CrN and CrAlN.